Effect of the Number of Micro-Osteoperforations on the Rate of Tooth Movement and Periodontal Response in Mice - Erdenebat, Tselmuun; Lee, Dong-Joon; Kim, Su-Jung; Choi, Yoon Jeong; Kim, Eun-Jung; Choi, Eun-Hack; Liu, Jing; Hwang, Chung-Ju; Jung, Han-Sung; Cha, Jung-Yul (Frontiers in Physiology, 2022)
Accelerated tooth movement can be achieved using micro-osteoperforations (MOPs) to stimulate regeneration of the alveolar bone during minimally invasive surgical trauma. However, there is currently no standardized protocol and limited reports regarding the side effects of MOPs based on biological evidence. This study sought to evaluate the biological effects of the number of MOPs on orthodontic tooth movement (OTM) and the potential risk for root resorption. Male CD1 mice were divided into 4 groups based on the number of MOPs, as follows: Sham; 0MOP+OTM; 2MOP+OTM; and 4MOP+OTM groups. Tooth movement distance and the number of osteoclasts were higher whereas bone volume and trabecular number were lower in the 4MOP+OTM group compared to those of the 0MOP+OTM group. Immunofluorescent assay analysis indicated that the 4MOP+OTM group was positively associated with rapid cementum regeneration and periodontal ligament tissue formation. Our findings revealed that the MOP procedure affected tooth movement and did not significantly contribute to root resorption, whereas it may promote constitutive activation of cementogenesis.